The influence of immigrant parents on the college decisions of Latinx community college students - Lopez, Monica (Kansas State University, 2022)
Latinx students are pursuing college at historically high rates; however, completion rates for this population are not keeping pace. With these students disproportionately attending community colleges, 2-year college leaders are striving to break down barriers and identify support systems that increase Latinx student success. Two factors found to influence students’ academic success are their generational status and participation of parents in their education. Involvement of parents has been linked to improved student academic achievement and motivation, but little research has focused on Latinx parent involvement with community college students. In addition, Latinx immigrants are less likely to have experience with U.S. higher education, but little is known about how this influences their children’s college going decisions. This qualitative phenomenological study aimed to provide an understanding of the collective influence of these factors by exploring the role immigrant parents play in the college decisions of Latinx first-generation community college students. This study used Yosso’s (2005) theory of community cultural wealth, derived from critical race theory, as a framework to explore the extent to which immigrant parents contributed to students’ acquisition of cultural capital. The study also focused on parental influence in three areas of decisions students make about college: (a) whether to go to college, (b) where to go to college, and (c) what to study in college. The researcher used a storytelling approach to conduct culturally contextualized, semistructured interviews with 17 first-generation Latinx community college students whose parents were immigrants to the United States. Through their testimonios and narratives, these students revealed how they universally sought and valued their parents’ input when making decisions about college, despite their parents’ lack of higher educational attainment. These students also demonstrated strong evidence that they had acquired a variety of forms of community cultural capital through their lived experiences and these made a difference in how they approach college. Findings from this study could point the way for community colleges to develop more inclusive pathways for Latinx immigrant parents to support their children in navigating the college experience, thereby supporting both in realizing their shared commitment to the “American dream.”
Keywords: Latinx; Community college students; First-generation college students; Immigrant parents